Ten women’s decision-making experiences in threatened preterm labour: Qualitative findings from the EQUIPTT trial - Carlisle, N.; Watson, H.A.; Kuhrt, K.; Carter, J.; Seed, P.T.; Tribe, R.M.; Sandall, J.; Shennan, A.H. (Sexual & reproductive healthcare, 2021)
•Women who present in threatened preterm labour are not fully involved in shared decision-making and have limited understanding about the predictive tests used in their care.•Pregnant women have busy lives and conflicting priorities which affect the decisions they make.•Women describe their threatened preterm labour symptoms as ‘period-like pains’. Clinicians should utilize this terminology which women understand and relate to. Clinical triage of women in threatened preterm labour (TPTL) could be improved through utilising the QUiPP App, as symptoms alone are poor predictors of early delivery. As most women in TPTL ultimately deliver at term, they must weigh this likelihood with their own personal considerations, and responsibilities. The importance of personal considerations was highlighted by the 2015 Montgomery ruling, and the significance of shared decision-making. Through qualitative interviews, the primary aim was to explore women’s decision-making experiences in TPTL through onset of symptoms, triage, clinical assessment, and discharge. Qualitative interviews were undertaken as part of the EQUIPTT study (REC: 17/LO/1802) using a semi-structured interview schedule. Descriptive labels of the coding scheme were applied to the raw transcript data. This coding scheme was then increasingly refined into key themes and allowed parallels to be made within and between cases. Ten ethnically diverse women who presented at six different London hospitals sites in TPTL were interviewed. Three final themes emerged from the data incorporating 10 sub-themes, ‘Seeking help’, ‘Being “assessed” vs making clinical decisions together’, and ‘End result.’ Women described their busy lives and the need to juggle their commitments. Participants drew comparisons between their TPTL symptoms and ‘period pain,’ contrasting to typical medical terminology. Shared decision-making and the clinician-patient relationship could be improved through clinicians utilizing terminology women understand and relate to. Women used language that highlighted the clinician-patient power balance. While not fully involved in shared decision-making, women were overall satisfied with their care.